Analysis of a spur gear in automative system using finite element software - Mohd Khairi, Mohammad (2013)
This study applied the Numerical Method Model to determine a characteristic for system gear. The most critical components in power transmission system are gearing system because in automotive industry gearing is commonly used in machines. In this study, Finite Element Method was used to analyze gears system. A metal-type material that was used to analyze was two different materials. The first one is gray cast iron because this metal is widely used in industry and the second one is steel 4130 or alloy steel that to know either this material suitable using in gearbox. Gear will be study in static structure condition to determine a stress, strain and also displacement to know which gear got maximum impact for every components gear system. For this analysis used the gearing in gearbox system, with different size, weight, and shape. Before analysis is done, a gear system was modeled/designed using the SolidWork software. Every each gear are draw only using SolidWork because SolidWork were very flexible to design anything with any direction (3D). This software was used for determine a stress, strain, and displacement in the meshing model condition. From the FEM analysis result at every component gear, it was found at gear six for Driven and at gear one for Driver that got highest value stress, strain and displacement at 1000 rpm. So different materials maximum impact at same place for stress, strain and displacement but their value is not same, for gray cast iron the maximum stress is 4397.26 N/mm (driven) and 6471.42 N/mm (driver). For alloy steel the maximum stress is 4329.62 N/mm (driven) and 4735.89 N/mm2 (driver). Conclusion is if the speed in term revolution per minute is low, so the stress, strain and also displacement value will be high for static studies